A PREVALENSI PENYAKIT TBC DI KABUPATEN MAJENE TAHUN 2020 - Budianto Wiryodinomo (Jurnal Kesehatan Marendeng, 2021)
Pulmonary tuberculosis is an infectious disease that can attack the lung parenchyma, caused by the bacterium Mycobacterium tuberculosis, the incidence of tuberculosis in Majene district is increasing which indicates the high rate of disease transmission. This study uses a descriptive method with a retroactive study approach that uses secondary data in 2020. Male gender is more susceptible to TB disease than female, age 46-65 years or productive age is the age most suffering from TB, more bacteriological diagnosis than clinically, and all TB patients are treated using OAT. The number of respondents in the study were 414 patients with tuberculosis, the majority of whom were male in productive age, with a bacteriological diagnosis type and then treated with category 1 OAT according to standards.